Jambolão (Syzygium cumini) desidratado por liofilização e secagem em leito de jorro: avaliação do impacto do processo de secagem e caracterização do potencial funcional do produto final - Araújo, Ana Luiza Macedo de (2014)
Tropical fruits have been extensively studied due to their functional potential attributed to the presence of natural bioactive compounds. The exotic fruit jambolan (Syzygium cumini) has been reported for its appreciable amount of phenolic compounds, especially anthocyanins and antioxidant capacity. Nevertheless, there are hardly any derived jambolan products in the Brazilian market. In addition to that, considerable volumes of fruit are lost due to their high perishability. Dried fruits have become an important fruit market segment due to its weight and volume reduction and decreased transportation and storage costs. Thus, this study evaluated the jambolan pulp submitted to spouted bed drying (JLJ) and lyophilization (JLI), besides assessing the drying impact on the final product. In order to achieve this, the process performance was calculated and compared, as well the physicochemical and bioactive characteristics (moisture, water activity (aw), solubility, hygroscopicity, density, color, structure through images obtained by scanning electron microscopy (SEM), concentration of bioactive (total phenolic compounds (TPC), anthocyanins, proanthocyanidins and ascorbic acid) and antioxidant activity. The results showed drying efficiency higher than 60% for both products and that JLJ group showed higher moisture and water activity when compared to the JLI group (p<0.05). The two types of drying were able to produce stable final product in the microbiological point of view, given that both showed aw < 0.6. The final products exhibited high solubility (73.7 to 81.6%) and low hygroscopicity (9.8 to 11.6%), desirable characteristics for dehydrated foods. Despite the losses caused by drying, the dried jambolan pulp by both methods showed high TPC (468.6 to 534.0 mg GAE/100g dm), anthocyanins (from 491.9 to 673.4 mg. eq. cyanidin-3-glicoside/100g dm), proanthocyanidins (66.9 to 76.6 mg QTE/g dm) and ascorbic acid (156.4 to 186.8 mg/100 g dm). Taken together, the results of this study reveal spouted dried and freeze dried jambolan pulp as bioactive-rich natural products with suitable physicochemical and functional characteristics to be used as food ingredients. The data also demonstrate the drying techniques as rational strategies for the exploitation of the exotic fruit jambolan